Level of Understanding of the Professional Organization of Guidance and Counseling Among Guidance and Counseling Students in the Special Region of Yogyakarta - Farozin, Moh; Suwarjo, Suwarjo; Purnama, Diana Septi; Sari, Widya Juwita; Widyastuti, Dian Ari; Sulastriningsih, Sulastriningsih; Hasna, Salma Salsabila; Hidayah, Nor; Hazima, Haura (citeus, 2025)
The purpose of this study is to determine or assess the degree of understanding of the Guidance and Counselling professional organization in the Special Region of Yogyakarta, as well as the disparities in understanding among students based on level and gender. This study involved 238 guidance and counseling students from the special region of Yogyakarta, Indonesia who had completed the guidance and counseling profession course. A test instrument was developed to assess student’s understanding of (1) Articles of Association and Bylaws of the Indonesian Guidance and Counseling Association, (2) Organizational Attributes of the Indonesian Guidance and Counseling Association, and (3) and the Ethical Code of Guidance and Counseling, consisting of 79 multiple choice questions. Validity was assessed through expert judgment and analyzed using Aiken’s V. Reliability was tested through a reliability trial with Split Half Reliability analysis. Study's findings showed that students in the Special Region of Yogyakarta have a